Training in Data Processing using Smart PLS Software - Eliyanti Agus Mokodompit; Kadeni Kadeni; Maria Lusiana Yulianti; Sugianto Sugianto; Leny Yuliyani (Lembaga Pengembangan Kinerja Dosen, 2023)
officers' limitations in their analysis of data at the population and civil registry service in Bandung. The majority of these issues are brought on by the apparatus's lack of knowledge and skill as well as the sparse availability of computers. The sub-district office does not have adequate data storage, and data management and display are not supported by technology. Implementation strategy using coaching and training. The instruction offered takes the form of fundamental knowledge on how to show district population data using Smart PLS. Its operations include instruction and support for using the Smart PLS application in the Cipadung Village to present and process data. To determine how well the trainees understood how to use the Smart PLS program, interviews and questionnaires were administered as part of the service. The customer assistance team provides clear and comprehensive explanations of the data display. The use of this Smart PLS software aids Kelurahan staff in comprehending and processing data. It is beneficial to sub-district authorities in their work with the taught apps.